Análise de materiais de mídias integradas do Programa Estadual de Qualificação Profissional, um programa da Secretaria do Emprego e Relações do Trabalho do Estado de São Paulo - Forte Junior, Reynaldo Antonio (2010)
This study examines textbooks and other multimedia materials produced for the Professional Qualification Program (Programa de Qualificação Profissional, PEQ, in Portuguese), one of the measures of the Department of Employment and Labor Relations (Secretaria do Emprego e Relações do Trabalho, SERT, in Portuguese) in the State of São Paulo, established in 2007 after a full diagnosis at the state level with the purpose of promoting workers -- or those looking for employment -- qualification. In search of evidences to corroborate this analysis, we seek to understand the articulations of SERT with their partners and the methodological approaches used in the creation and development of the course. In order to this, we followed a teachers training program at the Paula Souza Center, sponsored by FUNDAP. We took part in the PEQ students first reception at the Paula Souza Center and interviews were held with the mulimedia materials producers on TV Cultura and with the technicians of SERT. Moreover, important documentation from the Department of Employment and Labor Relations was read. In the period this research, some of the main activities of SERT were articulated projects in qualifying workers. For the development of the research and data analysis, a survey was applied to twenty-five teachers working in partner schools. Data collection looks for evidence of efficient taking in use of the multimedia materials and its suitability to students who are, in general terms, badly-off, low educated people with problems of self-esteem. Research data shows that a worker qualification program, when offered with a good methodological content and developed in multimedia materials is capable of availing unemployed workers in finding a new job. These actions are boosted by the diffusion in complementary media, by an institution responsible for social programs